Impact of two-way texting for refill reminders and refill set-up on a phenylketonuria (PKU) patient population. (21st September 2018) - Snyder, M.; Sager, B.; Ill, S.; Lachner, N.; Allen, D.; Peterson, J.; Budlong, H.
Abstract: Background: Fairview Specialty Pharmacy supports different rare disease patient populations, including PKU patients on oral sapropterin therapy. Often traditional forms of communication, including phone calls, are inconvenient for patients to set-up refill orders and may eventually lead to decreased adherence by not placing orders on time. PKU patients may experience less mental clarity with missed doses, and further exacerbate nonadherence. Additional methods for setting up refills, including two-way texting services make it more convenient for patients to set up refill orders and may lead to increased adherence. Objectives: To assess the impact of texting technology for refill reminders and order set up on adherence through measurement of refill rates in a specialty pharmacy patients. Methods: Inclusion criteria: Patients of Fairview Specialty Pharmacy with a diagnosis of PKU on sapropterin with access to texting services with consent obtained. Additionally, patients had to have a medication possession ratio (MPR) of less than 90% for inclusion within the study. Exclusion criteria: Patients without access to texting services were not able to participate. Patients unwilling to provide consent for enrollment were also excluded. Patients who did not have an established MPR or fill the record with Fairview Specialty Pharmacy were also excluded from analysis. The primary endpoint is a change in MPR of patients who enroll in the texting program over six months. Statistical Analysis was conducted utilizing a paired t -test to compare MPRs before and after enrollment in the texting program. Results: To date, 29 PKU patients have enrolled in texting services. Five patients having been enrolled long enough to get six-month MPR difference results. Six patients enrolled long enough to get three-month difference results. Those eligible patients enrolled in two-way texting for six months ( n = 5) saw an average increased MPR of 0.21 over that time period. Four patients showed an increased MPR ranging from increases in 0.08 to 0.53. One patient experienced a decreased MPR by −0.07. Those eligible patients enrolled in two-way texting for three months ( n = 6) saw an average increased MPR of 0.11 over that time period with all patients showing increases in MPR ranging from 0.05 to 0.15. Conclusions: Early data results show an increase in adherence by patients enrolled in two-way texting. Additional time and further analysis are needed to determine adherence impact on the overall pharmacy patient population.